(untitled) (The Pakistan Development Review, 1997)
It is a matter of great pleasure for me to participate in this Conference organised by the Pakistan Society of Development Economists. I am happy to note that in the past twelve years this Conference has become a key annual event for a serious discussion of economic and social issues. The presence here of a large number of distinguished academics, research workers, and policy-makers from within and outside the country demonstrates the significance of this important forum. I would like to avail of this opportunity to extend a warm and cordial welcome to Dr Nafis Sadik and other distinguished participants from abroad to Pakistan and wish them a pleasant and fruitful stay.